Concentrations of PAHs (Polycyclicaromatic Hydrocarbons) Pollutant in Sediment of The Banten Bay - Khozanah Munawir; Deny Yogaswara (BULLETIN OF THE MARINE GEOLOGY, 2017)
Banten Bay is end of stream for a few rivers from Banten mainland where many manufactures and petrochemical industries are built. This may give environmental pressure of water quality of the bay due to pollutant input, such as Polycyclic Aromatic Hydrocarbons (PAHs). This study is to identify those pollutants and determine their total concentration and distribution in sediments. Surface sediment samples were collected in four zones: inner coastline within the bay, middle bay, coastline off the bay and outer of the Bay in April 2016. PAH components were extracted and measured using a gas chromatography-mass spectrometry. Levels of total PAHs in sediments in inner coastline within the bay ranged between 0.381-2.654 ppm with an average of 1.288 ppm, middle of the bay ranged between 0.747-1.762 ppm with an average of 1.198 ppm, outer of the bay ranged between 0.192-1.394 ppm with an average of 0.921 ppm, and east coast of the bay ranged between 0.191-1.394 ppm and an average of 0.778 ppm. The levels of total PAH contamination is apparently lower than those of PAH threshold in sediments (i.e. 4.5 ppm).Keywords: PAHs (Polycyclic Aromatic Hydrocarbons), Banten Bay Teluk Banten merupakan muara dari beberapa sungai di daratan utama Banten yang sebagian besar berupa kawasan industri dan kegiatan lain sekitar laut. Kondisi ini berpotensi memberikan tekanan terhadap kualitas perairan Teluk Banten karena masukan bahan pencemar diantaranya senyawa Polisiklik Aromatik Hidrokarbon (PAH). Penelitian ini bertujuan mengidentifikasi PAH dan menentukan konsentrasi total dan distribusinya di sedimen. Pengambilan sampel sedimen permukaan pada April 2016 diempat zona: zona pantai bagian dalam teluk, bagian tengah teluk, pantai bagian luar teluk, dan bagian luar teluk. Konsentrasi PAH diukur menggunakan alat kromatografi gas spektrometer massa (GCMS). Konsentrasi total PAH dalam sedimen pantai bagian dalam berkisar antara 0,381-2,654 ppm dengan rata-rata sebesar 1,288 ppm. Bagian tengah teluk berkisar antara 0,747-1,762 ppm dengan rata-rata sebesar 1,198 ppm, bagian luar teluk antara 0,192-1,394 ppm dengan rata-rata sebesar 0,921 ppm dan pantai bagian timur teluk antara 0,191-1,394 ppm dengan rata-rata sebesar 0,778 ppm. Level pencemaran total PAH di perairan Teluk Banten dalam sedimen mengindikasikan masih lebih rendah dari standar bakumutu PAH dalam sedimen yaitu 4,5 ppm.Kata kunci: PAH (Polisiklik Aromatik Hidrokarbon), Teluk Banten